Farmer preferences for milpa diversity and genetically modified maize in Mexico: A latent class approach - Birol, Ekin; Villalba, Eric Rayn; Smale, Melinda (Cambridge University Press, 2009)
Maize originated in Mexico, where it is typically grown in association with other crops in themilpasystem. This ancient mode of production is practiced today in ways that vary by cultural context and agro-environment. We use a choice experiment to estimate farmers' valuation of three components of agrobiodiversity (crop species richness, maize variety richness, and maize landraces) in themilpasystem, and examine their interest in cultivating genetically modified (GM) maize. We apply a latent class model to data collected from 382 farm households in the states of Jalisco, Oaxaca, and Michoacán to analyze the heterogeneity of farmer preferences. We identify the characteristics of farmers who are most likely to continue growing maize landraces, as well as those least likely to accept GM maize. Findings have implications for debates concerning the introduction of GM maize and the design ofin situconservation programs in these sites.